Calcium doped BiFeO3 films: Rietveld analysis and piezoelectric properties - Goncalves, L. F. [UNESP]; Rocha, L. S.R. [UNESP]; Longo, E. [UNESP]; Simões, A. Z. [UNESP] (My University, 2018)
Pure and calcium modified CaxBi(1−x)FeO3 (x = 0.0, 0.1, 0.2, 0.30) thin films were fabricated on Pt(111)/Ti/SiO2/Si substrates by the soft chemical method. The crystal structure and physical properties of polycrystalline Ca2+-doped BiFeO3 samples have been investigated. Structural studies by XRD reveal the co-existence of distorted rhombohedral and tetragonal phases in the highest doped BiFeO3 where enhanced piezoelectric properties are produced by internal strain. XPS results show that the oxidation state of Fe was purely 3+, which is beneficial for producing a piezoelectric film with low leakage current. Piezoelectric properties are improved in the highest Ca-doped sample due to the coexistence in the crystal structure of BFO with a primitive cubic perovskite lattice with four-fold symmetry and a large tetragonal distortion within the crystal domain. This observation introduces piezoelectronics at room temperature by combining electronic conduction with electric and magnetic degrees of freedom which are already present in the multiferroic BiFeO3.